HEALTH SYSTEM UNDER PRESSURE ASSESSING THE IMPACTS OF FUNDING VOLATILITY ON MATERNAL, CHILD, AND INFECTIOUS DISEASE SERVICES IN NIGERIA - Tukur, Ismail; Almu, Bello; Suleman, Tijjani; Dauda, Shafiu; Gora, Jamilu Umar (FUDMA Journal of Sciences, 2026)
Nigeria's health system faces chronic funding instability; however, the impact of financing volatility on service delivery failures remains poorly understood. This systematic review examines the impact of funding volatility on maternal, child, and infectious disease services in Nigeria. Following PRISMA guidelines, we searched PubMed, Scopus, Web of Science, and institutional repositories for literature published between 2010 and 2026. From 1,247 initial records, 87 studies met the inclusion criteria. An integrated theoretical framework combining the WHO Health System Building Blocks and Health Financing Functions guided the analysis. Financing volatility operates through three mechanisms: revenue collection inadequacy with government spending below one percent of GDP, pooling fragmentation with out-of-pocket payments exceeding seventy percent of health expenditure, and purchasing inefficiency characterized by delayed budget releases. These cascade through the health system, producing medicine stock-outs in sixty-eight percent of facilities, health worker demoralization contributing to forty-five percent attrition in some areas, and catastrophic household expenditure affecting fifteen to twenty-five percent of families. Policy responses, for instance, the Basic Health Care Provision Funds, were affected by political economy constraints and governance fragmentation. Financing volatility fundamentally drives health system fragility in Nigeria. The study recommended to meet the 15% Abuja Declaration health funding target; subsidize insurance for pregnant women, children, and the poor; and require 40% female representation on facility committees and report equity-disaggregated data.
Keywords: Health Financing; Health Systems; Child and Maternal Death